The Savvy Survey #6c: Constructing Closed-Ended Items for a Questionnaire - Jessica L. Gouldthorpe; Glenn D. Israel (EDIS, 2014)
This 5-page fact sheet presents an overview of constructing closed-ended items for a questionnaire. It is part of the Savvy Survey Series. Written by Jessica L. Gouldthorpe and Glenn D. Israel, and published by the UF Department of Agricultural Education and Communication, April 2014.